A Critical Review of the Performance, Combustion, and Emissions ‎Characteristics of PCCI Engine Controlled by Injection Strategy and ‎Fuel Properties - Medhat Elkelawy; Hagar Alm ElDin Mohamad; Elshenawy Abd elhamid; Mahmoud El-Gamal (Journal of Engineering Research - Egypt)
As internal combustion engines (ICEs) produce serious emissions and a big part of greenhouse gases from fuel combustion. Due to the universal concerns about degradation in the ambient environment, limitations on exhaust emissions, depletion of petroleum reserves, and global warming, many strict regulations have been launched on the standard emissions released from engines. Premixed charge compression ignition (PCCI) is a promising technique to overcome these challenges in recent years which can simultaneously reduce NOx and soot emissions and substantially improve thermal efficiency. The PCCI combustion concept has the advantages of both SI and CI engines, like SI engines as the charge is premixed which produces low emissions and like CI engines the fuel-air mixture is auto-ignited as a result of compression which leads o high thermal efficiency. Normally, PCCI combustion is a single-stage combustion process achieved by employing early injection timing to increase the time available for mixing fuel and air by using single-fuel and split fuel (pilot/main) injection tactics, in which a large fraction of fuel burns in premixed combustion phase resulting in relatively lower in-cylinder temperatures compared to compression ignition (CI) combustion. Thus, the objective of this paper is to provide an inclusive review of the effects of fuel injection timings, ratios, pressure, and fuel properties on the PCCI engine combustion performance improvement and emission reduction, this review has been analyzed extensively based on the published studies to provide and discuss different strategies for the control of PCCI technique of combustion at wide range of speed and load.